Pemberdayaan Ibu Rumah Tangga Melalui Inovasi Susu Kedelai Aneka Rasa di Desa Kedungdadi: Pengabdian - Nataliawati, Rita; Galaharbang, Yanuangga; Indira , Irma; Yaumi, Sri; Qosim (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service aims to empower housewives in kedungdadi village, Sugio District, Lamongan Regency, through training in processing soy milk with innovative flavor variants and packaging improvements, in order to improve skills and economic independence based on local potential. The method used is a qualitative participatory approach with the Participatory Rural Appraisal (PRA) method, involving 30 housewives and local PKK members. The activities were carried out in two main sessions, namely counseling on the potential of soybeans as a nutritious food ingredient and training in making soy milk with chocolate, strawberry, and original flavors. The results of Community Service show that participants gained new knowledge regarding the potential for diversifying soybean products with high economic value. In addition, the enthusiasm of participants in participating in the training showed success in improving their soy milk processing skills and entrepreneurial potential. Some participants even plan to produce and market this innovative product more widely This Community Service concludes that empowerment based on local potential with a participatory approach is able to create household economic solutions, especially for housewives, and increase village economic independence through processed soybean products.